Benefits Of Distance Learning in Teaching Process (Eurasian Research Bulletin, 2021)
The article deals with the issues based on the role of distance learning in teaching process. The integration of distance education, in general, into the educational community, the inevitable virtualization of universities operating in the field of distance education, will lead distance learning of foreign languages to compulsory study not only in the context of independent discipline, but in combination with various courses. Based on the material of this work, it will increase the effectiveness of education in the field of learning foreign languages